Estudios antracológicos en los espacios de combustión del Alero Deodoro Roca - Ongamira (Córdoba) - Robledo, Andrés Ignacio, (South American archaeology series ;, 2016)
This paper deals with the study of the archaeological remains of charcoal to further understand the usage and handling of fire by human hunter-gatherer groups who inhabited, over time, the Ongamira valley, located in the Ischilin and Totoral provinces of Cordoba, Argentina.